Analisa Keuangan Usaha Mikro Kecil Menengah (UMKM) Produsen Makanan Tahu - Imam Baidlowi (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Finance is a very important part of a business, because the company will be able to run well and normally if the company's finances run normally. Regarding company finances, in this study researchers have conducted research related to the method of managing company finances in SMEs, traditional tofu food producers